Rapid enlargement of pulmonary benign metastasizing leiomyoma with fluid-containing cystic change: a case report - Takahiro Yanagihara; Naohiro Kobayashi; Tomoyuki Kawamura; Shinji Kikuchi; Yukinobu Goto; Hideo Ichimura; Yukio Sato (Surgical Case Reports, 2022)
Abstract Background Pulmonary benign metastasizing leiomyoma (PBML) is a rare disease that can occur in women with a history of uterine leiomyoma. Despite its benign histological features, like a malignancy, leiomyomas can on rare occasion spread to the lung. Typically, PBML presents with asymptomatic multiple solid lung nodules with slow tumor progression, following hysterectomy. Here, we present an atypical case with rapid enlargement of PBML with fluid-containing cystic change. Case presentation We experienced a case of a 49-year-old woman with bilateral lung nodules following hysterectomy. Two nodules in the right lung had cystic change with fluid in the tumors. Hormone therapy was initiated after surgical biopsy of the left lung confirmed a diagnosis of PBML. However, the cystic component of right upper lobe lesion enlarged rapidly over the following 7 months, and, considering the risk of malignant transformation or tumor rupture, right upper lobectomy was performed. Pathologically, the fluid-containing tumor was diagnosed as PBML. Conclusion Given the risk of rapid progression, we should carefully consider the surgical indications of fluid-containing PBML.